The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1115/1.1861915
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Vane Clocking in a One and One-Half Stage High Pressure Turbine

Abstract: Aerodynamic measurements were acquired on a modern single-stage, transonic, high-pressure turbine with the adjacent low-pressure turbine vane row (a typical civilian one and one-half stage turbine rig) to observe the effects of low-pressure turbine vane clocking on overall turbine performance. The turbine rig (loosely referred to in this paper as the stage) was operated at design corrected conditions using the Ohio State University Gas Turbine Laboratory Turbine Test Facility. The research program utilized unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…According to the early work from [55], the efficiency is achieved when the segments of the first vane wake avenue, released by the rotor, impinge on the leading edge of the second vane. The basic reason for this result is that the low momentum fluid coming from the first stage, collapse in the boundary layer of the second vane and for this do not affect the passage (among others, [56][57][58]), studied in detail the clocking effects driven by the stator secondary flows in a two stage subsonic and transonic turbines.…”
Section: Cascades Clockingmentioning
confidence: 99%
“…According to the early work from [55], the efficiency is achieved when the segments of the first vane wake avenue, released by the rotor, impinge on the leading edge of the second vane. The basic reason for this result is that the low momentum fluid coming from the first stage, collapse in the boundary layer of the second vane and for this do not affect the passage (among others, [56][57][58]), studied in detail the clocking effects driven by the stator secondary flows in a two stage subsonic and transonic turbines.…”
Section: Cascades Clockingmentioning
confidence: 99%
“…The turbine stage maximum efficiency condition occurs when the wake from the upstream vane row is positioned such that it impinges on the leading edge of the downstream vane. The minimum efficiency condition, typically out of phase with the optimum configuration by half a passage, occurs when the wake convects through the middle of the downstream vane passage [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the noise generated by blade interaction could be effectively reduced by properly adjusting the circumferential position of the rotor in a compressor. Later on, the clocking effect is proved to greatly affect the performances and CONTACT Chen-Xing Jiang jiangchenxing@hrbeu.edu.cn unsteady aerodynamic dynamics, and many investigators tried to find the optimal clocking position to maximize the efficiency and get the best transient behaviors (Behr et al, 2006;Dieter et al, 2005;Haldeman et al, 2005;Saren et al, 1998). In recent years, some researchers are focusing on the clocking effect in more areas.…”
Section: Introductionmentioning
confidence: 99%